New Zealand : Selected Issues. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues paper conducts a comparative analysis of the main determinants of GDP per capita growth in New Zealand and in other OECD countries to assess the relative importance of macroeconomic factors, institutional settings, and geographical location in New Zealand's growth performance during the last 30 years. The estimation results find strong support for the view that geographical isolation has significantly hampered growth in New Zealand. The paper also reviews the international experience with prefunding public defined-benefit pension schemes, with a focus on recent reforms in industrial countries-Canada, Ireland, Norway, and Sweden.